EVALUATION OF THE REVERBERATION TIME IMPROVEMENT IN A SPEAKING HALL - FLORIN MARIAN NEDEFF; MARCEL AGOP; EMILIAN FLORIN MOȘNEGUȚU; NARCIS BARSAN (Journal of Engineering Studies and Research, 2016)
To improve a room's acoustic parameters there have been studied several variants of acoustic materials and devices that can be placed on the ceiling of the hall. The main objective of the study was the reverberation time measurement and calculation. By using the acoustic panel made from polystyrene, covered with jute on the both sides, has ensured the largest reverberation time decrease. Thus, we can say that the analyzed room can be used for speech activity (courses, conferences etc.)